2019
DOI: 10.20944/preprints201908.0262.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Landscape Changes and their Impacts on Land Surface Temperature in Tropical Hill Stations in South Asia: A Case Study of Nuwara Eliya, Sri Lanka

Abstract: Although urbanization has contributed to improving living conditions, it has had negative impacts on the natural environment in the urbanized areas. Urbanization has changed the urban landscape and resulted in increasing land surface temperature (LST). Thus, studies related to LST in various urban environments have become a popular research topic. However, few LST studies focusing on the mountain landscapes (i.e. hill stations) have been carried out. The primary objective of this study is to investigate change… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…To study landslide hazards using modern methods, GIS-integrated multi-criteria analyses are currently being carried out all over the world, including in Sri Lanka. The study conducted by Ranagalage (2013) attempted to identify landslide risk zones in the Walapane divisional secretariat division in the Nuwara Eliya district using a GIS-based method. By analyzing the temporal and spatial patterns of landslides that occurred in the study area, high-risk, moderaterisk, and risk-free areas have been identified and plotted.…”
Section: Risk = Hazard × Exposure × Vulnerabilitymentioning
confidence: 99%
“…To study landslide hazards using modern methods, GIS-integrated multi-criteria analyses are currently being carried out all over the world, including in Sri Lanka. The study conducted by Ranagalage (2013) attempted to identify landslide risk zones in the Walapane divisional secretariat division in the Nuwara Eliya district using a GIS-based method. By analyzing the temporal and spatial patterns of landslides that occurred in the study area, high-risk, moderaterisk, and risk-free areas have been identified and plotted.…”
Section: Risk = Hazard × Exposure × Vulnerabilitymentioning
confidence: 99%